Population pharmacokinetics and exposure–response analyses of SAF-189s in Chinese patients with ALK+/ROS1+ non-small cell lung cancer - Liu, Yinhui; Tan, Yan; Hu, Lin; Li, Jinlong; Yang, Jiansong; Diao, Lei; Yang, Jin (Frontiers in Pharmacology, 2024)
Objective SAF-189s is a potent ALK/ROS1 inhibitor that is currently in clinical development for treating advanced ALK+/ROS1+ non-small cell lung cancer (NSCLC). Comprehensive population pharmacokinetics (PopPK) and exposure–response models were developed to evaluate the efficacy and safety of SAF-189s by integrating data from two clinical studies. Methods The PopPK model was developed using plasma concentration data collected from patients with ALK+/ROS1+ advanced NSCLC (n = 299) and healthy subjects (n = 24). The covariates (demographics, laboratory values, subject types, and concomitant medications) were evaluated to determine their potential influence on the between-patient variability in the pharmacokinetics of SAF-189s. Individual exposure values were then used to investigate the relationships with the efficacy endpoints (overall response rate (ORR), progression-free survival (PFS), and duration of response (DOR)) and key safety endpoints (adverse events of interest). Results The final PopPK model of SAF-189s was described by a one-compartment model with delayed first-order absorption and time-dependent elimination by allowing the clearance to decrease stepwise over time. Age was included as a covariate for apparent clearance (CL/F), while prior anti-cancer therapy in ALK+ patients (ALKPOT) was included for apparent volume of distribution (V/F). There were no apparent exposure–response relationships for any of the efficacy endpoints at doses of 80–210 mg. The relationship between exposure and safety suggested that a higher steady-state exposure was associated with more frequent incidences of hyperglycemia and proteinuria; the 210-mg dose group was also less tolerated than the other low-dose groups. Conclusion PopPK and exposure–response models were developed for SAF-189s, and their results demonstrate that SAF-189s exposures are at the plateau of exposure–response for efficacy. The 210-mg dose group had a significantly higher safety risk, while the 160-mg dose group was well-tolerated. Thus, 160 mg of SAF-189s once daily was selected as the recommended phase III dose for the ALK+/ROS1+ or ROS1+ NSCLC patients.